Assessment of selected perioperative parameters in patients undergoing laparoscopic and abdominal supracervical hysterectomy - Sokołowski, Jakub; Skręt-Magierło, Joanna; Kluz, Tomasz; Barnaś, Edyta; Sobolewski, Marek; Raś, Renata; Skręt, Andrzej (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction : Subtotal hysterectomy is a method of treatment of patients with mild changes in the uterine body. Laparoscopic methods are increasingly used in surgical gynaecology. One of the limitations of laparoscopy is the proper level of operating surgeon’s training, which may be assessed with the use of the learning curve. The aim of the study was to compare data regarding the perioperative period in patients who underwent subtotal hysterectomy with the two methods, and to establish a learning curve for laparoscopic subtotal hysterectomy. Material and methods: One hundred and twenty-seven patients qualified for subtotal hysterectomy due to mild disturbances in the uterine body participated in the study. The study was conducted at the Clinical Department of Gynaecology and Obstetrics of Fryderyk Chopin Provincial Specialist Hospital in Rzeszów in 2012-2013. Results : The time of laparoscopic subtotal hysterectomy is longer than that of the classical surgical procedure. Uterine myomas are the main indication for subtotal hysterectomy. Laparoscopic operation results in lower blood loss compared to the classical surgical method. The mean age of the patients operated due to mild changes in the uterine body is similar in both groups. Patients who are obese or have undergone Caesarean sections are more frequently qualified for the classical surgery. The study revealed a reduction in time of laparoscopic subtotal hysterectomy by ca. 31 minutes (33%). Conclusions : Laparoscopic subtotal hysterectomy is a method chosen by operating surgeons for patients with a lower perioperative risk. The period of the study made it possible to determine a learning curve for laparoscopic subtotal hysterectomy.